Blockade of Tim-3 binding to phosphatidylserine and CEACAM1 is a shared feature of anti-Tim-3 antibodies that have functional efficacy. (1st February 2018) - Sabatos-Peyton, Catherine A.; Nevin, James; Brock, Ansgar; Venable, John D.; Tan, Dewar J.; Kassam, Nasim; Xu, Fangmin; Taraszka, John; Wesemann, Luke; Pertel, Thomas; Acharya, Nandini; Klapholz, Max; et al.
ABSTRACT: Both in vivo data in preclinical cancer models and in vitro data with T cells from patients with advanced cancer support a role for Tim-3 blockade in promoting effective anti-tumor immunity. Consequently, there is considerable interest in the clinical development of antibody-based therapeutics that target Tim-3 for cancer immunotherapy. A challenge to this clinical development is the fact that several ligands for Tim-3 have been identified: galectin-9, phosphatidylserine, HMGB1, and most recently, CEACAM1. These observations raise the important question of which of these multiple receptor:ligand relationships must be blocked by an anti-Tim-3 antibody in order to achieve therapeutic efficacy. Here, we have examined the properties of anti-murine and anti-human Tim-3 antibodies that have shown functional efficacy and find that all antibodies bind to Tim-3 in a manner that interferes with Tim-3 binding to both phosphatidylserine and CEACAM1. Our data have implications for the understanding of Tim-3 biology and for the screening of anti-Tim-3 antibody candidates that will have functional properties in vivo .